The Influence of the Family Hope Program (PKH) and Non-Cash Food Assistance (BPNT) on Community Welfare in Pangkalpinang City - Devi Valeriani; Vebtasvili; Tiara Amiza (JAMBE: Jurnal Akuntansi Manajemen Bisnis dan Ekonomi, 2024)
In realizing community welfare, the government distributes social assistance programs. One of the programs that has been implemented by the government is the Family Hope Program (PKH) and Non-Cash Food Assistance (BPNT). This research aims to determine the influence of the Family Hope Program (PKH) and Non-Cash Food Assistance (BPNT) on the welfare of the community in Pangkalpinang City. This research uses secondary data and primary data. Secondary data was obtained from data on PKH and BPNT social assistance recipients from the Pangkalpinang Social Service. Primary data was obtained using questionnaires, observation and interviews. In this research, researchers used a quantitative approach with multiple linear regression analysis. The population in this study was 4196 recipients of PKH and BPNT social assistance in 2021. The sample in this study used the Slovin formula, namely 98 people. The research results show that the Family Hope Program (PKH) has a negative and significant effect on the welfare of the people in Pangkalpinang City and Non-Cash Food Assistance (BPNT) has a positive and significant effect on the welfare of the people in Pangkalpinang City.